The Needs of The Community's Sports Information System in The Industrial 4.0 - Glady Sukma Perdana; M. Torero Rigel Centeury; Ilham Ilham; Japhet Ndayisenga (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The importance of sports activity to public fitness must be supported through available sports facilities and infrastructure. This study was a descriptive research with mixed methods. Access facilities and sports infrastructure are essential factors vital to increasing people's interest in practising to enhance the community's physical health. This study aims to recognise the need for a sports information system in the city in industrial 4.0 that require human beings to improve their physical condition and health to stay productive. It has a shut connection with the availability of information systems and sports activities infrastructure accessible around the residence. The subjects of this research were 137 public of Yogyakarta city by convenient sampling. Data analysis techniques using descriptive and correlation among indicators-item themselves with Software SPSS.25. The results showed TCR in the Good category in each item that these indicate that there was a lack of a productive sports activities information system to locate the capability and sports activities infrastructure around the public, which affect the lack of public interest and participation in the exercise knowledge became strong management tools that help physical education, sports medicine, coaching training managers to decide how to improve peak of performance, to maintain the excellent quality of public health: This study is the first to apply to evaluate the needs of the Community's Sports Information System In The Industrial 4.0.